2017
DOI: 10.1371/journal.pbio.2001323
|View full text |Cite
|
Sign up to set email alerts
|

What makes a reach movement effortful? Physical effort discounting supports common minimization principles in decision making and motor control

Abstract: When deciding between alternative options, a rational agent chooses on the basis of the desirability of each outcome, including associated costs. As different options typically result in different actions, the effort associated with each action is an essential cost parameter. How do humans discount physical effort when deciding between movements? We used an action-selection task to characterize how subjective effort depends on the parameters of arm transport movements and controlled for potential confounding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 34 publications
7
136
0
Order By: Relevance
“…The metabolic rate was shown to influence body size, resource use, rate of senescence and survival probability (Berghänel et al, 2015; Brown et al, 2004; DeLong et al, 2010; Munch and Salinas, 2009; Strotz et al, 2018; Voorhies and Ward, 1999). Preserving muscle effort may thus represent an essential pursuit for the brain (Baraduc et al, 2013; Bramble and Lieberman, 2004; Carrier et al, 2011; Cheval et al, 2018a, 2018b; Farshchiansadegh et al, 2016; Huang et al, 2012; Inzlicht et al, 2018; Kurzban et al, 2013; Lee et al, 2016; Lieberman, 2015; Mazzoni et al, 2007; Morel et al, 2017; Pageaux, 2016; Pageaux and Gaveau, 2016; Selinger et al, 2015; Shadmehr et al, 2016; Walton et al, 2006; Wang and Dounskaia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic rate was shown to influence body size, resource use, rate of senescence and survival probability (Berghänel et al, 2015; Brown et al, 2004; DeLong et al, 2010; Munch and Salinas, 2009; Strotz et al, 2018; Voorhies and Ward, 1999). Preserving muscle effort may thus represent an essential pursuit for the brain (Baraduc et al, 2013; Bramble and Lieberman, 2004; Carrier et al, 2011; Cheval et al, 2018a, 2018b; Farshchiansadegh et al, 2016; Huang et al, 2012; Inzlicht et al, 2018; Kurzban et al, 2013; Lee et al, 2016; Lieberman, 2015; Mazzoni et al, 2007; Morel et al, 2017; Pageaux, 2016; Pageaux and Gaveau, 2016; Selinger et al, 2015; Shadmehr et al, 2016; Walton et al, 2006; Wang and Dounskaia, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cos and colleagues showed 547 that when humans make rapid choices between reaching actions, they tend to choose the one that 548 carries the lowest biomechanical cost (Cos et al, 2011. Morel and colleagues found that 549 biomechanics affects action selection too, but among duration, amplitude, direction and force, they 550 observed that movement duration is perceived as the greatest cost by subjects (Morel et al, 2017). 551…”
Section: Motor Costs Influence Motor and Perceptual Decision-making 534mentioning
confidence: 99%
“…99 Other recent work further shows that the costs associated with motor control bias decision making between actions. [100][101][102] While the impact of motor costs on decision making is not limited to action-based models-for instance, good-based models can account for motor costs through learning or association-the representation of options in a sensorimotor space provides a convincing and direct way for motor information to influence value.…”
Section: Behaviormentioning
confidence: 99%